Neurenteric Cyst with Alteration of Signal Intensity on Follow-up MR Images - Shakudo, Miyuki; Inoue, Yuichi; Ohata, Kenji; Tanaka, Saori (American Journal of Neuroradiology, 2001)
Summary: Intracranial neurenteric cysts are uncommon and usually have low intensity on T1-weighted MR images and high intensity on T2-weighted MR images. We report a case of a neurenteric cyst that was situated in front of the medulla oblongata and the size of which increased with alteration of MR signal from high to isointense compared with that of brain on T1-weighted images obtained 33 months after the initial MR images. We think that the signal change of the cyst was probably caused by a change of protein concentration.